PENGARUH METODE DISKUSI, PEMBERIAN TUGAS DAN MOTIVASI BELAJAR TERHADAP PENCAPAIAN KELULUSAN UJIAN NASIONAL DI SDN MAYANGAN 6 KOTA PROBOLINGGO - Endang Astutik (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This study aims to know the influence of discussion and task based teaching method and learning motivation on national exam achievement at SDN Mayangan 6 Probolinggo. Ninety (90) students were invoked in this study as participants. From the results, it showed that there were significant influences of discussion teaching method, task based, learning motivation and all together simultaneously on national exam achievement.